Comparing the Effectiveness of Schema Therapy and Acceptance and Commitment Therapy on Alexithymia in Women with Multiple Sclerosis - Gholizadeh, Fatemeh; Zangeneh Motlagh, Firoozeh; Bayat, Mohammad Reza (Mental Health and Lifestyle Journal, 2026)
The present study aimed to compare the effectiveness of schema therapy and acceptance and commitment therapy in reducing alexithymia among women diagnosed with multiple sclerosis. This applied, semi-experimental study employed a pretest–posttest–follow-up design with a control group. The statistical population consisted of women with multiple sclerosis who referred to the Tehran Multiple Sclerosis Society during 2024–2025. Using an available sampling method, 45 eligible participants were selected and randomly assigned to three groups: schema therapy, acceptance and commitment therapy, and a control group, each comprising 15 participants. The two experimental groups received ten 90-minute group intervention sessions based on standardized protocols, while the control group received no psychological intervention. Data were collected using the Toronto Alexithymia Scale. Descriptive statistics and repeated-measures analysis of covariance were conducted using SPSS version 26, with pretest scores entered as covariates. Inferential analyses revealed a statistically significant main effect of group on alexithymia scores at posttest and follow-up. Both schema therapy and acceptance and commitment therapy resulted in significant reductions in alexithymia compared with the control group (p < 0.001). Post-hoc comparisons indicated that schema therapy led to significantly greater reductions in alexithymia than acceptance and commitment therapy at follow-up (p < 0.001). The group-by-time interaction was significant, demonstrating differential patterns of change over time. Effect size estimates indicated a large effect for the group factor, and robust HC3 estimates confirmed the stability of the results. Both schema therapy and acceptance and commitment therapy were effective in reducing alexithymia in women with multiple sclerosis; however, schema therapy demonstrated superior and more sustained effects, suggesting its particular suitability for addressing deep-seated emotional processing deficits in this population.